182k views
5 votes
Pls help I’ll put in 25

Pls help I’ll put in 25-example-1

1 Answer

3 votes

given -2(x + 1) = 5x + 4 - x ( distribute left side )

-2x - 2 = 4x + 4 ( simplifying both sides )

subtract 4x from both sides

- 6x - 2 = 4 ( add 2 to both sides )

- 6x = 6 ( variable by itself on left side )

divide both sides by - 6

x =
(6)/(-6) = - 1

as a check, substitute x = - 1 into the equation and if both sides are equal then it is the solution.

left side = - 2(-1 + 1 ) = - 2 × 0 = 0

right side = (5 × - 1) + 4 - (- 1) - 5 + 4 + 1 = 0

hence x = - 1 is the solution



User Megapoff
by
5.5k points